CONDITIONS OF TRANSFORMATION OF INNOVATIVE ENTREPRENEURSHIP INTO THE FACTOR OF REGIONAL POTENTIAL OF STRATEGIC COMPETITIVENESS - Vartsaba , V.I.; Hudzovata, L.M.; Zavadiak , Ya.S. (The actual problems of regional economy development, 2020)
The article is devoted to the conditions of transformation of the regional economy into a competitive system on the basis of intensification of innovation activity. The purpose of the study is to review the world experience of transformation of innovation into a competitive regional advantage, which will determine the conditions under which innovative entrepreneurship takes the form and content of the determining factor of the potential of territorial competitiveness. The following methods were used in the research process: categorical analysis in outlining the essence of the concept of regional viability, scientific abstraction in tracking the patterns of formation of regional competitiveness, causal induction in identifying the causes and consequences of certain factors on the level of innovation activity in the region, etc. It is proposed to define regional life as a set of efforts of territorial authorities, business operating in the region, the society of the region, other regional actors to carry out activities, strengthen development potential and build regional strategic competitiveness. It is highlighted the experience of Silicon Valley (USA) in the formation of regional competitiveness. It is constructed the triangle of conditions for the transformation of innovative entrepreneurship into a factor of competitiveness, within which the first condition is defined as management, which is a convergence of regional and business interests. The second is the availability of human potential capable of working in high-tech companies. The third condition is the creation of a field of national culture, which serves as a «broth» for the generation of new ideas and ways of their implementation. The practical implementation of the current conditions allows territorial authorities to develop an adequate regional strategy and use the innovation component to increase the region's competitiveness potential.